Determinants of Students' Decisions to Use Paylater Digital Financial Products - Lutfillah, Novrida Qudsi; Hapsari, Aziizah Putri; Candrawati, Triesti (Universitas Muhammadiyah Jakarta, 2024)
The use of digital financial technology is increasingly widespread among society, especially among students who are digitally active. One product that is increasingly popular is PayLater. This research aims to analyze the influence of digital financial literacy, lifestyle, social influence, and ease of use on the decision to use PayLater among students in Malang City. The t test is used as a data analysis method. The unit of analysis in this research is students who live in Malang, totaling 106 respondents. The research results show that digital financial literacy, lifestyle, social influence, and ease of use influence students' decisions to use digital financial products such as PayLater. It is hoped that this research will provide a deeper understanding of the factors that influence the use of PayLater among students and the implications for future financial management policies and practices.